A Critical Review of the Leadership Ethics of God's Servants in Resolving Church Leadership Conflicts - Solihin Bin Nidin (Formosa Journal of Multidisciplinary Research, 2023)
Ethics and leadership are two things that cannot be separated from a leader, both a public leader and a Christian leader. The pastor is a servant of God as well as a leader of the people or congregation. The life of a servant of God or a church leader must be an example for those he leads. A leader must equip himself with various competencies needed in ministry for the development and growth of the church. A leader must have pedagogical competence, professional competence, personal competence, social competence and spiritual competence.